2006
DOI: 10.1002/hep.21384
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate protects rat liver sinusoidal endothelial cells from ethanol-induced apoptosis: Role of intracellular calcium and nitric oxide

Abstract: In alcoholic liver disease, ethanol-induced damage to sinusoidal endothelial cells (SECs) appears to be important in the progression of liver damage. However, little is known about the mechanisms responsible for protection of SECs against ethanol-induced injury. To elucidate the role of sphingosine 1-phosphate (S1P), which is stored in platelets and may be released from them on their activation, we investigated the effect of S1P on rat liver SECs in primary culture. Pretreatment of cells with 1 mol/L S1P atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…Thus, the modulation of ceramide generation through ASMase mediating TNF/Fasinduced hepatocellular death may be a promising therapeutic approach to steatohepatitis [143], hepatic I/R damage [24] or alcohol-induced liver injury, in part, through activation of GCS and subsequent ganglioside generation that may target mitochondria weaken by depletion of mGSH [see 8 and references therein]. Finally, S1P has been shown to protect liver sinusoidal endothelial cells from ethanol-induced apoptosis, while the antiapoptotic role of SK through S1P formation has been involved in the protection of stellate cells in bile duct ligation-induced hepatic fibrosis [149,150]. Hence not only the generation of ceramide but its metabolism into antiapoptotic S1P derivative through concerted action of CDases and SK may have an important role in nonparenchymal cell fate and hence fibrogenesis.…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Thus, the modulation of ceramide generation through ASMase mediating TNF/Fasinduced hepatocellular death may be a promising therapeutic approach to steatohepatitis [143], hepatic I/R damage [24] or alcohol-induced liver injury, in part, through activation of GCS and subsequent ganglioside generation that may target mitochondria weaken by depletion of mGSH [see 8 and references therein]. Finally, S1P has been shown to protect liver sinusoidal endothelial cells from ethanol-induced apoptosis, while the antiapoptotic role of SK through S1P formation has been involved in the protection of stellate cells in bile duct ligation-induced hepatic fibrosis [149,150]. Hence not only the generation of ceramide but its metabolism into antiapoptotic S1P derivative through concerted action of CDases and SK may have an important role in nonparenchymal cell fate and hence fibrogenesis.…”
Section: Liver Diseasesmentioning
confidence: 99%
“…S1P is already known to modulate endothelial functions, such as attenuate increase in vascular permeability by regulating junctional complexes (13). It has also been shown to block in vitro endothelial cell death induced by H 2 O 2 (14), ethanol (15), and serum deprivation (16). We recently showed that S1P protects human microvascular endothelial cells (HMEC-1) from radiation-induced apoptosis (17).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the endogenous lipid derivative, sphingosine-1-phosphate (S1P), has emerged as a potentially im-portant regulator of EC barrier function (Itagaki and Hauser, 2003;McVerry and Garcia, 2004;Finigan et al, 2005;Seol et al, 2005;Zheng et al, 2006). Upon a variety of stimuli leading to protein C activation, S1P is generated from sphingosine through the action of ubiquitous sphingosine kinase (SK).…”
mentioning
confidence: 99%